INNISFREE’S BRAND IMAGE THROUGH JEJU ISLAND CAMPAIGNS - Kezia Tansilia Melvioni; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study aims at revealing the message conveyed by the verbal and non-verbal expressions in cosmetics advertisement videos, in this case, two advertisement videos by a cosmetic brand called, Innisfree. In examining the message, firstly, the writer identifies the verbal and non-verbal expressions used in the advertisements analyzed. Secondly, she discloses the denotative and connotative meanings of those expressions. In so doing, she uses two main theories, namely, the process of signification and Peirce’s triadic modes of sign. The findings reveal that the verbal expressions in the two advertisement videos show that Innisfree is a symbol of a natural beauty and an icon of cosmetic that use nature-based ingredients. Meanwhile, the non-verbal expressions in the two advertisements constantly highlighting on Jeju island’s natural beauty, as the main source of Innifree’s products that should be preserved. Thus, Innisfree encourages its customer to conserve natural environment. In conclusion, Innisfree is a company that produces an inner and outer-beauty.